Minority languages and translator training: what Tibetan programmes can tell us - Roberta Raine (JoSTrans: The Journal of Specialised Translation)
The relationship between minority languages and translator training programmes is a very new and under-researched area of inquiry in Translation Studies. The People's Republic of China, which has 55 different minorities within its borders, is an ideal country in which to examine this issue. This paper focuses on the Tibetan language, one of the minority languages in China for which translator training programmes are available. The paper first provides a brief overview of translator training programmes in China in general, and then examines the situation of Tibetan-Chinese training programmes in Tibet and other parts of China, linking these to the job market for translators in these regions. The paper then explores a unique parallel development outside of China of Tibetan-English translator training programmes that have been established for students of Tibetan Buddhism who wish to train as interpreters or translators. The contrast of these two widely differing sets of training programmes reveals the divergent market forces at work that spur the development of such programmes, and also highlights the role that translator programmes may play in the survival of lesser-used languages.